BONECAS NA NOITE: HISTÓRIAS COTIDIANAS DE TRAVESTIS E TRANSEXUAIS - Ferrareze, Rafael Bozzo (2015)
This study began first with the theoretical discussions about gender, identity, culture, community development among others, followed by the preparation of this work. The study site was the non-profit organization (Rebirth), intended to defend the human rights of LGBT`s. The target audience of this were four transvestites and transsexuals three with the overall objective to present the everyday stories of transvestites and transsexuals in prostitution or whoring denizens of Reborn ong in the city of Ponta Grossa/PR, and specific objectives address the discussions on transvestite and transgender identities, everyday stories in the night these social actresses, their perceptions about a trans culture amid pontagrossense community as well as their involvement in the local community development. The problem of our study, guiding this work, focused on showing the everyday stories of transvestites and transsexuals whose work prostitution, bringing even during the same as guide their customer relationships, their becomings, who are these people and what these social actresses have to show us about their daily lives. The methodology was qualitative research being supported the semi-structured interviews or unstructured and as background material for the construction of the information received, the technique of oral history. For the processing of this information was used narrative analysis. In the midst of this work is also displayed on the doll term path to reference the social actresses participants of our research and the theoretical mediators used to deepen our discussions, mediators such as: gender identity, transvestites, transsexuals, becoming, ecology knowledge, stigma, community and community development.